Mengenalkan Metode Empiris, Kuantitatif, dan Eksperimental Dalam Penelitian Hukum Tata Negara - Abiyoso, Yunani (Jurnal Konstitusi & Demokrasi, 2025)
Almost all constitutional law research applies the doctrinal method to analyze normative texts and legal logic. In the context of the development of constitutional law, this method has limitations in evaluating the effectiveness of legal norms in societal reality. This article proposes the need for a paradigm shift in the use of constitutional law research methods, which should not only rely on a doctrinal approach but also integrate empirical methods, to align the needs of constitutional law studies with the dynamics of the Indonesian state after 25 years of constitutional amendments. There are three alternative methods that can be integrated with the doctrinal method: the empirical method, the quantitative method, and the experimental method. Thru the application of various methods, constitutional law research is expected to present an analysis of normative texts based on empirical evidence to propose constitutional recommendations.